The expressional disorder of the renal RAS mediates nephrotic syndrome of male rat offspring induced by prenatal ethanol exposure. (1st May 2018) - Zhu, Yanan; Zuo, Na; Li, Bin; Xiong, Ying; Chen, Haiyun; He, Hangyuan; Sun, Zhaoxia; Hu, Shuangshuang; Cheng, Hui; Ao, Ying; Wang, Hui
Highlights: PEE induces fetal kidney developmental retardation and adult nephrotic syndrome. PEE causes the disorder of the renal classic and non-classical RAS. PEE inhibits the gene expression of renal AT2R in male offspring via epigenetic mechanism. Ethanol directly contributes to the dysregulation of the renal RAS. Ethanol directly inhibits the expression of H3K27ac in the AT2 R promoter in the primary metanephric mesenchyme cells. Abstract: This study aimed to prove that prenatal ethanol exposure (PEE) can induce nephrotic syndrome in male rat offspring and to explore the underlying intrauterine programming mechanisms. Pregnant Wistar rats were intragastrically administered ethanol (4 g/kg d) from gestational day (GD) 9 to GD 20, and the male fetuses were delivered by cesarean section at GD20 and the male adult offspring were euthanized at postnatal week (PW) 24. In vitro, the primary metanephric mesenchyme cells were treated with ethanol at concentrations of 15–60 mM. The results indicated that the kidneys of adult offspring in the PEE group exhibited glomerulosclerosis as well as interstitial fibrosis. The levels of serum creatinine and urine protein were elevated; the serum total cholesterol level was increased and the serum albumin concentration was reduced. In the fetal kidney, developmental retardation was presented in the PEE group via pathological examinations, accompanied by the expressional inhibition of the glial-cell-line-derived neurotrophic factor/c-ret tyrosine kinase receptor (GDNF/c-ret) signaling pathway. Although serum angiotensin II (Ang II) level and the gene expression of renal angiotensin-converting enzyme (ACE) were increased in the PEE group, the expression of renal angiotensin II type 2 receptor (AT2 R) was significantly inhibited, accompanied by a reduction in the H3K27ac level on the AT2 R gene promoter. In the non-classical renin-angiotensin system (RAS), the expression of renal angiotensin converting enzyme 2 (ACE2) and Mas receptor (MasR) were inhibited in the PEE group. The above changes of the classical and non-classical RAS all sustained from utero to adulthood. In vitro, ethanol elevated the gene expression of ACE and angiotensin II type 1a receptor (AT1a R) whereas it reduced the expression of AT2 R, ACE2, and MasR, accompanied by a reduction in the H3K27ac level on AT2 R gene promoter. Taken together, these results suggested that PEE can induce fetal kidney developmental retardation and adult nephrotic syndrome, and direct regulation of ethanol to the renal RAS was involved in the mechanism of nephrotic syndrome induced by PEE.